The role of PKM2-mediated metabolic reprogramming in the osteogenic differentiation of BMSCs under diabetic periodontitis conditions - Yanlin Zhu; Yuhan Yang; Yuyan Lan; Zun Yang; Xiang Gao; Jie Zhou (Stem Cell Research & Therapy)
Abstract Background Diabetes mellitus (DM) and periodontitis have a bidirectional relationship, with each being a high-risk factor for the other. Prolonged hyperglycemia exacerbates periodontal inflammation and disrupts bone homeostasis. Pyruvate kinase M2 (PKM2), a key enzyme in glycolysis, is involved in metabolic reprogramming, but its role in osteogenesis under high-glucose (HG) inflammatory conditions remains largely unknown. This study aimed to investigate the effects of HG and inflammation on bone marrow mesenchymal stem cells (BMSCs) under indirect co-culture conditions and to explore how PKM2 regulates metabolism and mitochondrial function during osteogenic differentiation in HG inflammatory environments, elucidating its role in diabetic periodontitis (DP). Methods Expose BMSCs to conditioned medium (CM) collected from RAW264.7 cells stimulated with HG and/or lipopolysaccharide (LPS). BMSCs functionality was assessed using CCK8, EdU, Annexin V-PI apoptosis assay, alkaline phosphatase (ALP), and Alizarin Red S (ARS) staining. Metabolic characteristics were evaluated through Seahorse assays, lactate production, glucose uptake, and ATP measurements. Mitochondrial function was assessed via JC-1, and ROS staining, Mito-Tracker staining, and transmission electron microscopy (TEM). Gene and protein expression were analyzed by quantitative real-time PCR and western blotting. In vivo therapeutic effects of shikonin were validated via micro-CT and histological staining in a diabetic periodontitis mouse model. Results In vitro experiments demonstrated that HG inflammatory conditions impaired the survival of BMSCs, suppressed osteogenic differentiation, and induced metabolic reprogramming. This reprogramming was characterized by enhanced glycolysis, impaired oxidative phosphorylation (OXPHOS), abnormal upregulation of PKM2 expression, and mitochondrial dysfunction accompanied by morphological alterations. Shikonin effectively reversed these adverse effects by inhibiting PKM2 tetramerization, rescuing the loss of osteogenic function in BMSCs. The therapeutic potential of shikonin was confirmed in the diabetic periodontitis mouse model. Conclusion PKM2 impairs the osteogenesis of BMSCs by affecting metabolism and mitochondrial function, suggesting it as a potential therapeutic target for diabetic periodontitis.